Filsafat Politik Ibnu Rusyd - Halimatuzzahro Halimatuzzahro (UIN Sunan Kalijaga Yogyakarta, 2017)
During this time Ibn Rushd is known for his Aristotelian philosophy, he is also the greatest commentator on the works of Aristotle. In his political philosophy we will find different things, because in political philosophy he commented on the Republic rather than Aristotle’s Politics. In his political book which is a commentary of Plato’s Repub- lic namely a-arûri fi as-Siyâsah, Ibn Rushd has more in common with Plato than with Aristotle. Nevertheless, Ibn Rushd continued to use the demonstrative method he obtained from Aristotle as a guide in commenting on the Republic. In addition, Ibn Rushd’s political book is also born of the reality of government that he considered not good. This made Ibn Rushd’s political book not only an academic one, but a response to the political situation of his time. His great name as a Muslim philosopher and also a faqih is still clearly visible in his political work which has shari’ah nuances. His ability to make Shari’ah one of the foundations of good and right government made him different from the two Greek philosophers.[Selama ini Ibnu Rusyd dikenal dengan filsafatnya yang beraliran Aristotelian, Ia juga merupakan komentator terbesar atas karya-karya Aristoteles. Dalam filsafat politiknya kita akan menemukan hal berbeda, karena dalam filsafat politik ia mengomentari Re- public bukan Politics Aristoteles. Dalam kitab politiknya yang merupakan komentar dari Republic Plato yaitu a-arûri fi as-Siyâsah, Ibnu Rusyd memiliki lebih banyak kesamaan dengan Plato dibanding dengan Aristoteles. Walaupun demikian, Ibnu Rusyd tetap menggunakan metode demosntratif yang ia dapat dari Aristoteles sebagai pegangan dalam memberikan komentar terhadap Republic. Selain itu, buku politik Ibnu Rusyd juga terlahir dari realita pemerintahan yang ia anggap tidak baik. Hal tersebut menjadikan buku politik Ibnu Rusyd bukan hanya merupakan komentar yang bersifat akademik saja, tetapi merupakan sebuah respon dari keadaan politik pada masanya. Nama besarnya sebagai seorang filsuf muslim dan juga seorang faqih masih terlihat jelas dalam karya politiknya yang memiliki nuansa syari’at. Kemampuannya untuk menjadikan syari’at sebagai salah satu pondasi pemerintahan yang baik dan benar menjadikannya berbeda dengan kedua filsuf Yunani tersebut.]